Evaluation of Hybrid System for Domestic Power Generation by Harvesting of Rainwater - PERUMAL, PRASSHANTH (IRC, 2017)
Annually, Malaysia receives a large amount of rainfall. As a result, a large amount of water is literally going down the drain. Rainwater, if harvested and taken full advantage of, could be a highly sustainable source of renewable energy. Rainwater is an energy source inherent with potential due to the abundance of its availability and widespread accessibility. Besides that, the purchasing and consumption of energy is becoming increasingly costly. Businesses and even private consumers are constantly looking for ways to reduce energy consumption and wastage in order to cut costs. Rainwater, being a free and abundant source of energy, should therefore be looked to as an alternative source of energy. This project tackles both the aforementioned issues by utilising harvested rainwater for the purpose of domestic power generation. This can be achieved via a fairly simple concept that this project implements. Rainwater is collected in rainwater harvesting tanks placed on elevated support structures. Rainwater from these tanks are then run though hydro turbines and collected again in ground level water tanks.